EXPERIENCE OF THE METALLURGICAL ENTERPRISE FOR EARLY GRANTING OF SOCIAL HOLIDAY ON PREGNANCY - Екатерина Ливерьевна Базарова; Наталья Алексеевна Рослая; Илья Семенович Ошеров; Наталья Владимировна Шевелева (Медицина в Кузбассе, 2021)
Objective – the state of health of pregnant women at a large metallurgical enterprise. The aim of the study is a medical and demographic assessment of the effectiveness of the early provision of social maternity leave at a large metallurgical enterprise in the Sverdlovsk region.